Comparison of Online Versus Classroom Delivery of an Immunization Elective Course - Porter, Andrea L. (American Journal of Pharmaceutical Education, 2014)
Objective. To compare performance and preferences of students who were randomly allocated to classroom or online sections of an elective course on immunization. Methods. Students were randomly assigned to either the classroom or online section. All course activities (lectures, quizzes, case discussions, vaccine administration, and final examination) were the same for both sections, except for the delivery of lecture material. Assessment. Students were surveyed on their preferences at the beginning and end of the semester. At the end of the semester, the majority of students in the classroom group preferred classroom or blended delivery while the majority of students in the online group preferred blended or online delivery (p<0.01). Student performance was compared at the end of the semester. There was no significant difference for any of the grades in the course between the 2 sections. Conclusion. There was no difference in student performance between the classroom and online sections, suggesting that online delivery is an effective way to teach students about immunization.